Public Security, Police Intelligence and Biometry:: Possibilities for Dialogue. (Brazilian Journal of Police Sciences, 2026)
This article discusses the use of biometrics, particularly in the application of fingerprints and facial recognition (prosopographic examination), as an auxiliary tool for police intelligence activity. Thus, two cases are presented involving the use of false documents (identity cards), where the analysis of the fingerprints by the Federal Police Fingerprint Experts, together with the AFIS system (Automated System of Identification of Fingerprints), allowed to establish links between the occurrences, identify potential victims and, ultimately, assist in investigative procedures through Forensic Intelligence. In light of this context, using the teachings of Bourdieu Bakthtin and Shecaira, among other researchers in philosophy, sociology and criminology, the concepts of Public Security, Intelligence and Police Intelligence from a perspective that aims to safeguard Constitutional Rights, such as the Right to Identity.
Keywords: Public Security; Police Intelligence; Fake Documents; Fingerprint Expert